Peningkatan Produktivitas Tenaga Kerja Melalui Program Insentif Pada PT. Kirana Windu Surulangun Rawas - Syafitri, Anggia; Nurbaiti, Nurbaiti; Diana, Diana (Asosiasi Dosen Akuntansi Indonesia, 2022)
PT. Kirana Windu on the Sumatran Cross Road Kilometer 98 Kec. Rawas Ulu Kab. Musi Rawas Utara has not implemented an incentive program for employees who produce more than company standards in maximizing labor productivity. This study aims to implement an incentive program to encourage labor productivity at PT. Kirana Windu Surulangun Rawas. The research method uses descriptive analysis techniques, namely data analysis by providing explanations and giving predicates to the variables studied according to actual conditions. The results of research conducted at PT. Kirana Windu shows that the incentive program using the Straight Piecework Plan method is profitable for the company because the wages given to workers are smaller than other incentive programs, which are Rp. 10,912,445,647. In addition, the Straight Piecework Plan incentive program is easier for company management to understand so that the program is well-organized. Even so, the workforce will remain motivated with additional incentives from the company, so that the labor productivity ratio will increase